Total sialic acid, total protein and total sugar levels in serum and saliva of oral squamous cell carcinoma patients: A case control study - Nidhi Dhakar; Madhusudan Astekar; Mahesh Jain; Swati Saawarn; Nisheeth Saawarn (Wolters Kluwer Medknow Publications, 2013)
Background: Detection of cancer at an early stage is of utmost importance to decrease the morbidity and mortality of the disease. Apart from the conventional biopsy, non-invasive methods like analysis of serum and saliva may provide cost-effective approach for screening a large population. Tumor markers are a major part of secondary prevention and thus, the detection of malignancies. The aim of this study was to evaluate total sialic acid (TSA), total protein and total sugar (TS) in serum and saliva of oral squamous cell carcinoma (OSCC) and controls to assess their role as a diagnostic marker. Materials and Methods: Unstimulated whole saliva and sera were collected from 40 squamous cell carcinoma patients and 20 controls. Serum and salivary TSA, total protein and TS estimation was carried out. This was correlated with clinical stages and histopathological grades of OSCC. The data obtained was analyzed statistically using Chi-square test, ANOVA and Student's t-test with SPSS statistical software. Results: A highly significant rise in the salivary sialic acid, serum sialic acid and serum protein was noted in OSCC subjects compared to controls. Salivary protein, serum and salivary sugar did not show any significance. Furthermore, serum and salivary sialic acid levels were found to be significantly increased with increasing level of histopathological grading. Conclusion: The present study showed a significant increase in serum sialic acid, salivary sialic acid and serum protein from control to OSCC and suggests that these markers may be reliable in diagnosis and predicting prognosis.